Exploring the Effects of “What” (Product) and “Where” (Website) Characteristics on Online Shopping Behavior - Mallapragada, Girish; Chandukala, Sandeep R.; Liu, Qing (Journal of Marketing, 2016)
Understanding factors that influence online shopping and managing consumer relationships is not a trivial task for firms, considering the many pertinent factors that influence behavior, including the product being shopped (i.e., the “what”) and the context of the website itself (i.e., the “where”). This study investigates the impact of these characteristics on an online transaction's basket value, after incorporating the role of other aspects of the browsing process including page views and visit duration. The authors estimate a multivariate mixed-effects Type II Tobit model with a system of equations to explain variation in shopping basket value, using data involving 773,262 browsing sessions resulting in 9,664 transactions across 43 product categories from 385 unique websites. The results support the assertions that contextual factors are associated with online browsing. For example, a website's scope in terms of product variety is associated positively with visit durations and basket values but negatively with page views. Furthermore, a website's communication functionality is positively associated with basket value for hedonic products. Insights suggest managerial implications involving product and website strategies for online retailers.